Ontological Metaphor in Adele’s Selected Song Lyrics - Bindra Gisca Maya (English Department, Faculty of Humanities, Andalas University, 2017)
This article discusses the ontological metaphor found in Adele’s songs. It aims to determine the types of ontological metaphor and their meanings. Lakoff and Johnson’s theory of conceptual metaphor is used in analyzing the data. From 21 data collected entity and substance metaphor (11 data) is the type of metaphor mostly used followed by container (6 data), 6 data belong to personification (6 data). And entity and substance metaphor (2). By using metaphor, the writer of those song lyrics wants to give deep impression and deeper meaning rather than to use literal language.